2018
DOI: 10.1016/j.jsps.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Top 10 most used drugs in the Kingdom of Saudi Arabia 2010–2015

Abstract: Medications usage has become a significant part of contemporary life. Many studies indicate that there is an excessive use and a considerable waste of medicines. This descriptive study aims at identifying the most used medicines in Saudi Arabia from 2010 to 2015 according to the statistics of specialized companies in the field. Comparison of the most commonly used drugs with those in the United States aims at clarifying similarities and differences. The results showed that the use of antibiotics and analgesics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 35 publications
5
39
0
Order By: Relevance
“…In addition, antibiotic overuse is a leading factor, among the many complex factors, of antibiotic resistance [7]. In Saudi Arabia between 2010 and 2015, antibiotics were the second most commonly used drugs [8]. The pattern of antibiotic consumption in one of the major hospitals in Saudi Arabia for admitted patients shows that around two thirds of the prescriptions were broad-spectrum antibiotics where one third of the cases were without documented diagnoses [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, antibiotic overuse is a leading factor, among the many complex factors, of antibiotic resistance [7]. In Saudi Arabia between 2010 and 2015, antibiotics were the second most commonly used drugs [8]. The pattern of antibiotic consumption in one of the major hospitals in Saudi Arabia for admitted patients shows that around two thirds of the prescriptions were broad-spectrum antibiotics where one third of the cases were without documented diagnoses [9].…”
Section: Introductionmentioning
confidence: 99%
“…OTC drug use in Saudi Arabia is reportedly high [7]. Some studies have suggested that the prevalence rates of substance abuse in Arab countries are accelerating quickly as a result of the extraordinarily fast economic development [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…PPIs ranked as the 6th most commonly dispensed therapeutic category in the United States, whereas 3rd most commonly dispensed therapeutic category in Ireland and Saudi Arabia during 2018. [ 10–12 ] However, PPIs cost, acid inhibiting agents and the frequency of prescribing has had a substantial bearing on prescribing budgets globally. [ 13,14 ] Costs on PPIs was €595 million in England in 2006 and €4.5 billion on one PPI (Nexium ® ‐Esomeprazole) in the United States in 2009.…”
Section: Introductionmentioning
confidence: 99%